La exportación de oro y su incidencia en el Producto Bruto Interno del Perú durante el período 2000-2017 - Chota Castillo, Zintia Yessenia (2019)
The mining sector in Peru is one of the pillars of the Peruvian economy and exports. Mining contributes 20% of fiscal revenues, contributes around 15% of national GDP and 60% of exports. The main objective of the following investigation is to determine the Incidence of Gold Export in the Gross Domestic Product of Peru during the period 2000-2017. Among the specific objectives are to evaluate the Evolution of Gold Exports in its different items, describe the variation of the GDP of Peru. The problem of the investigation is to know What has been the Incidence of the Gold Export in the Gross Domestic Product of Peru during the period 2000-2017? Therefore, the hypothesis proposed is that the Gold Export positively affects the Product Gross Domestic of Peru causing it to increase during the period 2000-2017. Regarding the research design, a non-experimental, longitudinal and descriptive approach has been chosen. The results showed from the econometric logarithmic model that when increasing the Gold Export by 1%, the GDP dependent variable will increase by 0.13%, in conclusion, the Gold Export affects the Peruvian GDP, thus finding a positive and statistically significant relationship.